Does long-term culture favor normal clonogenic cells from interferon-treated patients with chronic myelogenous leukemia? - Pasternak, Günter; Schultheis, Beate; Heissig, Beate; Hörner, Susanne; Sick, Christian; Hehlmann, Rüdiger (Leukemia, 1999)
We have tested whether peripheral blood mononuclear cells (PBMNCs) from interferon (IFN)-treated patients may lose residual BCR-ABL sequence-positive progenitor cells when long-term cultured for 35 days on allogeneic stromal cells. IFN-treated patients have low white blood cell counts and a fair number of BCR-ABL-negative colony-forming cells in the peripheral blood. Particularly, IFN responders show increased numbers of normal hematopoietic cells. We have quantitatively analyzed progenitor cells in PBMNCs of IFN-treated patients by combining the clonogenic assay in semisolid medium with interphase fluorescent in situ hybridization (FISH). Thus, the identification is possible of the BCR-ABL status of colony-forming progenitor cells. In IFN-treated patients, the number of BCR-ABL-positive CFCs is considerably decreased and BCR-ABL-negative CFCs appear in the peripheral blood. We could show that after LTC for 35 days of the same PBMNCs on irradiated allogeneic normal stromal cells residual BCR-ABL sequence-positive CFCs were still present. In some cases the relative number of BCR-ABL sequence-positive CFCs was found to be increased after LTC. A minor proportion of blood samples from IFN-treated patients did not give rise to CFCs after LTC on allogeneic stromal cells (three of 10 patients). Inter- and intraindividual variations can be found with regard to loss or gain of BCR-ABL sequence-positive colonies after LTC. We conclude that early CML progenitor cells persist in the peripheral blood of IFN-treated patients and that a certain proportion may survive long-term culture.